Perspectivas educacionais e novas demandas contribuições da telecolaboração - Garcia, Daniela Nogueira de Moraes (Editora Oficina Universitária, 2020)
The world today is experiencing one of its most critical moments in its history with the Covid-19 pandemic. In Education, 1.5 billion students were left without classes and in their homes, according to Unesco data, with schools closed in 191 countries and 63 million teachers being affected. We had to suddenly transform our face-to-face practices into remote activities, a difficult task as the vast majority did not have and continue to have no training for this. But if on the one hand we have a serious crisis, we can turn it into a great opportunity for change. The current moment is one of the richest in terms of means of interaction, communication and access to information, made possible by advances in digital technologies. We have many resources, but we lack strategies and training that allow us to use them in the construction of contextualized, meaningful and inclusive learning environments. In this direction, this work portrays relevant experiences to understand how we can establish activities that use technologies in teacher training, in language teaching projects that consider contexts, the multicultural perspective and the meanings for students. In addition, it highlights the noblest role of a teacher, which is the process of mediation and collaboration to build the knowledge of its students. At the present time, this book can be a light for educators as it demonstrates that technology, when well used, is a valuable tool for creating rich learning environments, whether face-to-face, virtual or hybrid.